EFFECT OF COLD-ROLLING ON THE TENSILE PROPERTIES OF (AL2O3)P/AL COMPOSITES - LEE, JC; SUBRAMANIAN, KN (ELSEVIER SCIENCE SA LAUSANNE, 1992)
Cold rolling of extruded 6061 Al alloy composite reinforced with 10% of Al2O3 particulates along the transverse direction results in more uniform distribution of the particulates. This rolling is associated with a considerable amount of damage to the particulates. Room temperature tensile tests carried out on the rolled composites showed, with increasing reduction in rolling, significant decrease in strength and insignificant change in fracture strain along the longitudinal (extruded) direction. However, the same properties increased with increasing reduction in rolling along the transverse (rolling) direction. Such behaviors of rolled composites are analyzed on the basis of redistribution of the particulate clusters, disappearance of the particulate free zones, particulate damage, and the contribution of the individual particulate to the strengthening with the achievement of uniform distribution.
Keywords: REINFORCED ALUMINUM; MATRIX COMPOSITES; ALLOYS